The Gray Zone in Thyroid Nodules: Atypia of Undetermined Signifi cance/ Follicular Lesion with Unknown Signifi cance - Selami Ilgaz Kayılıoğlu; Ufuk Utku Göktuğ; Tolga Dinç (Open Journal of Thyroid Research - Peertechz Publications, 2017)
Major purpose of the management of thyroid nodules is to distinguish between malignant nodules and the benign ones. Nodules with the cytology result Atypia of Undetermined Significance or Follicular Lesion of Undetermined Significance are still a diagnostic challenge. Initial presentation of the Bethesda System was based on 7% diagnosing rate and around 5-15% malignancy rate for these nodules; however, clinical practice presents with higher rates for both variables. Recent studies showed that when these nodules are grouped by cytological features; compared with the architectural atypia group, the cytological atypia group has a significantly higher risk of malignancy. Cytological sub-classification, ultrasonographic evaluation and genetic tests in selected cases should be used in the management of these nodules.